2017
DOI: 10.1186/s13018-017-0621-0
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal morphine versus femoral nerve block for pain control after total knee arthroplasty: a meta-analysis

Abstract: BackgroundThis meta-analysis aims to illustrate the efficacy and safety of intrathecal morphine (ITM) versus femoral nerve block (FNB) for pain control after total knee arthroplasty (TKA).MethodsIn April 2017, a systematic computer-based search was conducted in PubMed, EMBASE, Web of Science, Cochrane Database of Systematic Reviews, Cami Info. Inc., Casalini databases, EBSCO databases, Verlag database and Google database. Data on patients prepared for TKA surgery in studies that compared ITM versus FNB for pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Our ITMB data are similar to those of previous laparoscopic and open surgery reports [5,[22][23][24]; thus, ITMB is a feasible and practicable form of pain relief (yielding a lower pain score and lower opioid requirement). Moreover, it was not associated with serious complications (such as nerve injury) during or after surgery, and was better than RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 86%
“…Our ITMB data are similar to those of previous laparoscopic and open surgery reports [5,[22][23][24]; thus, ITMB is a feasible and practicable form of pain relief (yielding a lower pain score and lower opioid requirement). Moreover, it was not associated with serious complications (such as nerve injury) during or after surgery, and was better than RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 86%
“…A urological study suggested that multimodal pain control via intrathecal bupivacaine/morphine may optimally improve the quality of early recovery and reduce postoperative pain, being associated with less pain during exertion and fewer bladder spasms (compared to a control group) [5]. Our ITMB block data are similar to those of previous laparoscopic or open surgery reports [5,[14][15][16]; the ITMB block was a feasible and practicable form of pain relief, not associated with serious complications (such as nerve injury) during or after surgery, and was better than the RSB or IV-PCA alone.…”
Section: Discussionsupporting
confidence: 75%
“…One retrospective study comparing intrathecal and peripheral postoperative blocks for patients, including those undergoing robotic pancreatoduodenectomy, suggested that intrathecal morphine administration was signi cantly associated with a lower pain score and a lower opioid requirement soon after surgery than were a tap block and a quadratus lumborum nerve block [14]. In an orthopedic study, intrathecal morphine seemed to be more reliable in terms of analgesic e cacy and opioid-sparing than a femoral nerve block [15]. In a gynecological study, the addition of intrathecal bupivacaine to intrathecal morphine signi cantly improved postoperative pain relief, but the addition of rectus sheath bupivacaine to intrathecal morphine did not afford additional analgesia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Total knee replacement has achieved good therapeutic effects in easing pain and improving functional outcomes for patients with rheumatoid arthritis or knee osteoarthritis [1,2]. Approximately 100, 000 TKR operations are performed each year in the UK [3].…”
Section: Introductionmentioning
confidence: 99%